Pengaruh Model Problem Based Learning Berbantuan Smart Ludo Terhadap Kemampuan Berpikir Kritis Peserta Didik Materi Kekayaan Budaya Indonesia - luma, anri; fanny, arif (Universitas Jambi, 2025)
This study aims to improve the critical thinking skills of students at the elementary school level by applying the problem-based learning model assisted by smart ludo. This study uses quantitative research with a quasi-experimental research method (Quasi Experimental Design) .The design used is Nonequivalent Control Group Design. The population in this study were all class IV SDN Menanggal 601 Surabaya. The sampling technique used was Probability sampling. The type of sampling used is simple random sampling. The data collection method used was the test method. The results can be seen from the mean post-test value in the experimental class which is 80.00 and the mean post-test value in the control class which is 61.15. This shows that there is a difference between classes that use a problem-based learning model with smart ludo and classes that use a problem-based learning model without media. Based on the results of the Independent sample t-test output, the sig. (2 tailed) value is 0.000 <0.05, then H0 is rejected and H1 is accepted, meaning that there is an effect of the Problem Based Learning model assisted by smart ludo on the critical thinking skills of students on the material of Indonesia's cultural wealth.